Assessing Orinoco river sediment discharge trend using MODIS satellite images. (April 2019) - Gallay, Marjorie; Martinez, Jean-Michel; Mora, Abrahan; Castellano, Bartolo; Yépez, Santiago; Cochonneau, Gérard; Alfonso, Juan A.; Carrera, Juan Manuel; López, José Luis; Laraque, Alain
Abstract: The aim of this study was to derive the Surface Suspended Sediment Concentration (SSSC) and river sediment discharge (for the period 2000-2016) along the Orinoco River reaches using MODIS remote sensing data. A single SSC retrieval algorithm was calibrated using HYBAM long term monitoring program data (n = 183). The comparison of satellite and field measurements showed a RMSE of 32%, corresponding to a mean absolute error of 21 mg l −1 . These results supported the use of MODIS sensors to monitor the SSSC at six virtual stations in the middle and lower reaches of the Orinoco River. The highest mean SSSC were found downstream of the Meta River (101 mg l −1 ) and of the Apure River (99 mg l −1 ), which provide the major sediment input to the Orinoco main stream. The lowest mean SSSC was found upstream of the Meta River (42 mg l −1 ). In the lower reach, at Ciudad Bolivar station we assessed a mean SSSC of 88 mg l −1 . MODIS-derived and ground-derived assessments of the annual sediment discharge show very fine agreement, within −2%. Coupling satellite-derived SSSC estimates and river discharge monitoring data, we calculated the Orinoco River sediment discharge at Ciudad Bolivar station between 2001 and 2016. For a mean Orinoco River discharge of 33, 320 m 3 .s −1, the sediment loads varied from 75 to 103 Mt.yr −1, with a mean value of 89 Mt.yr −1 (RSD of 9%) corresponding to a sediment yield of 91–125 t.km −2 yr −1 with no positive or negative trends over the observed period. Highlights: The Orinoco River surface suspended sediment concentration (SSSC) was estimated using MODIS sensors. The results shown a general increasing trend in SSSC with, however, spatial and temporal variations. The suspended sediments loads and yields have shown no significant change over the observed period. These results are of particular interest in the context of increasing or decreasing trends observed in most South American rivers.